2018
DOI: 10.1111/jcpt.12684
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol ameliorates haematological parameters, oxidant/antioxidant biomarkers and pulmonary function tests in patients with sulphur mustard‐induced lung disorders: A randomized double‐blind clinical trial

Abstract: Two-month treatment with CAR reduced inflammatory cells and oxidant biomarkers, whereas increased antioxidant biomarkers and improved PFT tests in SM-exposed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…in other experimental models for carvacrol. In fact, the anti‐inflammatory potential of carvacrol has been evaluated in two recent clinical trials, indicating that its clinical use is effective for the management of inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in other experimental models for carvacrol. In fact, the anti‐inflammatory potential of carvacrol has been evaluated in two recent clinical trials, indicating that its clinical use is effective for the management of inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…From these mechanisms, carvacrol and thymol are able to attenuate the leucocyte migration characteristic of the first phase of tissue repair, as demonstrated by Riella et al [12] and Karami et al [20] for thymol, and by Pina et al [44] and Guimarães et al [40] in other experimental models for carvacrol. In fact, the anti-inflammatory potential of carvacrol has been evaluated in two recent clinical trials, [45,46] indicating that its clinical use is effective for the management of inflammatory conditions. Subsequently, the proliferative phase begins, which is divided into four stages: re-epithelialization, angiogenesis, formation of granulation tissue and deposition of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized clinical trial demonstrated that carvacrol (a monoterpenic phenol and principle compound of volatile oil in different plants species) at a dose of 1.2 mg/kg per day decreases blood cells counts including neutrophil after 1 and 2 months of treatment compared with the placebo group (Khazdair, Alavinezhad, & Boskabady, ).…”
Section: Neutrophil‐targeted Drug Delivery In Respiratory Diseasesmentioning
confidence: 99%
“…There were eight studies that used the following doses for oral administration: three animal studies used 73 mg/kg (one dose) (Şen et al, 2014); 80 mg kg −1 day −1 (for 7 days) (Ozer et al, 2017); and 25 and 50 mg/kg (for 7 days) ( Barnwal et al, 2018); four studies with humans used a dose of 1.2 mg kg −1 day −1 (all four studies offered carvacrol for 2 months) (Alavinezhad, 2018;Khazdair et al, 2018;Khazdair & Boskabady, 2019a;Khazdair & Boskabady, 2019b); and one study used a dose of 1 or 2 mg kg −1 day −1 (for 1 month) (Ghorani et al, 2019). In administration via nebulization, the concentration was 240 μl in 5 ml of saline solution (one dose) (de Carvalho et al, 2019).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…orally. All of the human studies that analyzed chronic lung injury (Khazdair et al, 2018;Khazdair & Boskabady, 2019a, 2019b) used a dose of 1.2 mg kg −1 day −1 of encapsulated carvacrol.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%